Sengketa Internasional Indonesia Vs Uni Eropa Tentang Larangan Ekspor Bijih Nikel - Muhammad Renal Anugrah Saputra; Muzafar Mukhtar; Muhammad Haikal Akbar; Al-Qhiani Fadia Putri; Dewi Rahmawati Gustini (Peneliti.net, 2023)
Natural resources are quite rich in Indonesia, especially in the mining industry. Nickel is one of Indonesia's promising and high-value export commodities. Silvery-white and shiny nickel is a naturally occurring metallic element. Because of its wide distribution within the Earth's core and crust, nickel is the sixth most abundant element. As one of Indonesia's unique mining commodities, nickel has great competitiveness from 2010 to 2020. As a result, the European Union (EU) sued Indonesia in 2020 at the World Trade Organization (WTO) over the ban on nickel ore exports by the Indonesian government as the ban on palm oil exports which was considered to have the most severe environmental damage. Indonesia currently has alternatives related to problems through the WTO provisions, in article XX (g) and also Indonesia can prove that the policy does not harm the European Union.